Review of monitoring systems for stored grains in a modified atmosphere - Louis Labrot–Rhodes; Eric Campo; Pierre Poujaud (Heliyon)
Losses during grain storage have become unacceptable owing to the growing needs of the world's population and climate problems. Monitoring systems in combination with measured data analytics can help to prevent insect or mold damage to stored grains, whatever the storage technique used. Indeed, it is necessary to identify and understand the risks associated with storage and the quantities available to ensure optimal storage when assessing the relevance of solutions. First, we discuss and compare existing monitoring solutions. Next, we examine smart agriculture approaches under development for post-harvest monitoring of warehouses or silos, which is currently well covered by solutions proposed by companies or research laboratories. However, the comprehensive review indicates that there is currently a lack of solutions for monitoring grains stored in hermetic bags in modified atmospheres, particularly those enriched with carbon dioxide. This solution seems interesting because it does not use any phytosanitary products and has proven its effectiveness. Different works on the development of these monitoring solutions are presented. Finally, the various challenges raised are discussed.